Pediatric brain tumors: A neuropathologist's approach to the integrated diagnosis - Viaene, Angela N. (Frontiers in Pediatrics, 2023)
The classification of tumors of the central nervous system (CNS) is a rapidly evolving field. While tumors were historically classified on the basis of morphology, the recent integration of molecular information has greatly refined this process. In some instances, molecular alterations provide significant prognostic implications beyond what can be ascertained by morphologic examination alone. Additionally, tumors may harbor molecular alterations that provide a therapeutic target. Pediatric CNS tumors, in particular, rely heavily on the integration of molecular data with histologic, clinical, and radiographic features to reach the most accurate diagnosis. This review aims to provide insight into a neuropathologist’s approach to the clinical workup of pediatric brain tumors with an ultimate goal of reaching an integrated diagnosis that provides the most accurate classification and informs prognosis and therapy selection. The primary focus will center on how histology and molecular findings are used in combination with clinical and radiographic information to reach a final, integrated diagnosis.